2010
DOI: 10.5536/kjps.2010.37.4.389
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Performances and Carcass Traits in Three Major Meat-Type Duck Strains in Korea

Abstract: The present experiment was carried out to compare performance, carcass characteristics and meat quality among three major meat-type duck strains in Korea. Two commercial duck (CD) strains, produced from parent stocks (PS) (Cherry Valley and Grimaud), and F1 strains, self-produced by farmers, were used in an 8-week feeding experiment. Both feed conversion ratio and production index were significantly higher in Cherry Valley strain compared with the other two at the ends of 6 and 8 weeks (p<0.05). However, no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
3
6
1
3
Order By: Relevance
“…The data of FI and FCR also highlighted this age as the best age for better growth and feed efficiency across all the crossbreds. The BWG of large type KND was lower when compared to that of commercial ducks in some previous research ( NRC, 1994 ; Lee and Lee, 2005 ; Bang et al, 2010 ) and it was similar to the BWG of KND reported by Kim et al (2012) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The data of FI and FCR also highlighted this age as the best age for better growth and feed efficiency across all the crossbreds. The BWG of large type KND was lower when compared to that of commercial ducks in some previous research ( NRC, 1994 ; Lee and Lee, 2005 ; Bang et al, 2010 ) and it was similar to the BWG of KND reported by Kim et al (2012) .…”
Section: Discussionsupporting
confidence: 80%
“…The initial higher BW of BA crossbred as compared to AB crossbred might be due the fact that BA crossbred used B line that has higher productivity as a female rather than A line which has lower productivity ( Kim et al, 2012 ; Hong et al, 2012 ). The weekly BW of commercial Pekin duck which were reported in the previous research are around 650 g at 2 wk-old ( Lee and Lee, 2005 ; Bang et al, 2010 ), 2,000 g at 4 wk-old ( Lee and Lee, 2005 ; Bang et al, 2010 ), 3,000 g at 6-wk old ( Farhat and Chavez, 2000 ; Adeola, 2003 ; Lee and Lee, 2005 ; Bang et al, 2010 ), and 3,700 g at 8-wk old ( Bang et al, 2010 ; Kim et al, 2010 ). Generally the BW of KND is much lower than that of commercial meat type duck.…”
Section: Discussionmentioning
confidence: 89%
“…초기 토종오리는 평 균 체중 1.8 kg으로 소형이거나, 종자의 무분별한 이용으로 근친화되어 외모와 체중(평균 체중 2.6 kg)의 균일도가 떨어 진다 (Kim et al, 2012 (Bang et al, 2010). Choo et al(2014) Attia et al(2013)과 본 시험에서는 사양 기준 에 따른 차이를 보였는데, 본 연구에서는 한국가금사양표준 (KFSP, 2012)에 맞춰 사양기준을 정한 반면에, Attia et al (2013)는 연구 기관의 임의로 사양 기간을 나눈 것으로 사료 된다.…”
Section: 국내 오리 산업은 오리고기 생산량과 소비량에 맞추어 꾸준 히 성장하여unclassified
“…또한 품종에 관계 없이 오리의 사료섭취량을 조사한 다른 연구들 (Bang et al, 2010;Choo et al, 2014)과도 유사하게 나타났다. 그러나 같 은 토종오리 계통으로 조사한 Kim et al(2012a) 과 Heo et al (2015)의 결과를 비교하였을 때 Kim et al(2012a) …”
unclassified